Spectrum of novel mutations found in Waardenburg syndrome types 1 and 2: implications for molecular genetic diagnostics. Issue 3 (18th March 2013) - Wildhardt, Gabriele; Zirn, Birgit; Graul-Neumann, Luitgard M; Wechtenbruch, Juliane; Suckfüll, Markus; Buske, Annegret; Bohring, Axel; Kubisch, Christian; Vogt, Stefanie; Strobl-Wildemann, Gertrud; Greally, Marie; Bartsch, Oliver; et al.
Abstract : Objectives: Till date, mutations in the genes PAX3 and MITF have been described in Waardenburg syndrome (WS), which is clinically characterised by congenital hearing loss and pigmentation anomalies. Our study intended to determine the frequency of mutations and deletions in these genes, to assess the clinical phenotype in detail and to identify rational priorities for molecular genetic diagnostics procedures. Design: Prospective analysis. Patients: 19 Caucasian patients with typical features of WS underwent stepwise investigation of PAX3 and MITF . When point mutations and small insertions/deletions were excluded by direct sequencing, copy number analysis by multiplex ligation-dependent probe amplification was performed to detect larger deletions and duplications. Clinical data and photographs were collected to facilitate genotype–phenotype analyses. Setting: All analyses were performed in a large German laboratory specialised in genetic diagnostics. Results: 15 novel and 4 previously published heterozygous mutations in PAX3 and MITF were identified. Of these, six were large deletions or duplications that were only detectable by copy number analysis. All patients with PAX3 mutations had typical phenotype of WS with dystopia canthorum (WS1), whereas patients with MITF gene mutations presented without dystopia canthorum (WS2). In addition, one patient with bilateral hearing loss and blue eyes with iris stroma dysplasia had a de novo missense mutation (p.Arg217Ile) in MITF . MITF 3-bp deletions at amino acid position 217 have previously been described in patients with Tietz syndrome (TS), a clinical entity with hearing loss and generalised hypopigmentation. Conclusions: On the basis of these findings, we conclude that sequencing and copy number analysis of both PAX3 and MITF have to be recommended in the routine molecular diagnostic setting for patients, WS1 and WS2. Furthermore, our genotype–phenotype analyses indicate that WS2 and TS correspond to a clinical spectrum that is influenced by MITF mutation type and position.